Prevotella melaninogenica Meningitis and Abscess: A Complication of the Removal of a Midline Dermoid Cyst - Garcia, Megan B.; Kunz, Anjali N. (Journal of Pediatric Infectious Diseases, 2020)
Prevotella species are gram-negative anaerobic commensal bacteria of the oropharynx, which frequently cause periodontal disease but are otherwise rarely implicated in serious bacterial infections. Cranial dermoid cysts are benign neoplasms that grow along the planes of the embryonic neural tube closure. In infants, they most commonly present in frontal locations, including periorbital, nasal, and within the anterior fontanelle. Although dermoid cysts are slow growing, usually uncomplicated, and easily treated definitively with surgical excision, cranial cysts located on the midline are associated with a higher risk for persistent dermal sinus tract with intracranial extension of the tumor. We describe a case of a 10-month-old male patient with an occipital midline dermoid cyst with intracranial extension, infected with Prevotella melaninogenica, and complicated by intracranial abscess formation and meningitis.This case highlights two unusual disease entities: the uncommon occipital location of a dermoid cyst, and complications of that cyst caused by a serious bacterial infection with a normal oral flora. We discuss the recommendation for neuroimaging prior to surgical excision of a midline dermoid cyst, given the risk for dermal sinus tract with intracranial communication. We also discuss potential mechanisms for bacterial inoculation of this cyst with Prevotella melaninogenica. This pathogen has not previously been reported as a complication of dermoid cysts.
Keywords: Prevotella; dermoid cyst; dumbbell dermoid